Finding the context indigenous innovation in village enterprise knowledge structure: A topic modeling - Retno Kusumastuti; Mesnan Silalahi; Anugerah Yuka Asmara; Ria Hardiyati; Vishnu Juwono (Journal of Innovation and Entrepreneurship, 2022)
Indigenous people have deep local knowledge of environmental sustainability and natural resource utilization, which are sources of innovations that often are drivers for economic growth in rural areas. This study explores the knowledge structure of indigenous innovation in village enterprises through content analysis of research publications. The resulting knowledge structure can be used to set up a roadmap for the studies on village enterprise and in a broader context to build metadata as a foundation for an evaluation system of village enterprise. The authors deploy topic modeling and co-word analyses to scrutinize 775 village enterprise research articles from the Scopus database and 665 paper from ScienceDirect. In the topic modeling, topic models village enterprises are setup. The topics found are local ownership (such as market and property), land, services (housing, health care), economy and public policy, financial service micro-credit, environmental pollution control, local business sustainability, social entrepreneurship, and household income, bioenergy based electrification, and bumdes management. Four sectors of the natural resource-based indigenous economy were identified: traditional food production, bio-energy for fuel and electricity, agriculture, and tourism. The topic models are used to comprehend knowledge structure in the village enterprises, whereby the focus is to uncover the context of indigenous village enterprise and its states of the art.
Keywords: 650; Indigenous people; Knowledge structure; Topic modeling analysis; Village enterprise